Clinically meaningful changes on depressive symptom measures and patient‐reported outcomes in patients with treatment‐resistant depression. (22nd January 2021) - Turkoz, Ibrahim; Alphs, Larry; Singh, Jaskaran; Jamieson, Carol; Daly, Ella; Shawi, May; Sheehan, John J.; Trivedi, Madhukar H.; Rush, A. John
Abstract: Objective: To use the Clinical Global Impression‐Severity (CGI‐S) scale to estimate clinically meaningful and clinically substantial changes as measured using the Montgomery‐Åsberg Depression Rating Scale (MADRS), the Sheehan Disability Scale (SDS), and the Patient Health Questionnaire‐9 (PHQ‐9) in patients with treatment‐resistant depression (TRD). Methods: Pooled data were derived from two 4‐week, randomized, active‐controlled studies evaluating esketamine nasal spray (ESK) plus oral antidepressant (OAD) or OAD plus placebo nasal spray (PBO) in adults with TRD ( N  = 565). CGI‐S, MADRS, SDS, and PHQ‐9 scores were obtained at baseline and over 4 weeks of treatment. In this post hoc analysis, change scores on the MADRS, SDS, and PHQ‐9 that corresponded to a clinically meaningful (1‐point) or clinically substantial (2‐point) change on the CGI‐S scale were identified. Results: Clinically meaningful changes in CGI‐S scores after 28 days corresponded to 6‐, 4‐, and 3‐point changes from baseline on the MADRS, SDS, and PHQ‐9, respectively. Similarly, a 2‐point CGI‐S score change (clinically substantial change) corresponded to a 12‐, 8‐, and 6‐point change on the MADRS, SDS, and PHQ‐9, respectively. The proportion of patients showing substantial clinical improvement in the ESK plus OAD group versus the OAD plus PBO group after 28 days of treatment favored ESK plus OAD: 69.0% vs 55.3% (MADRS), 64.5% vs 48.9% (SDS), and 77.1% vs 64.7% (PHQ‐9). Conclusion: We provide a basis for identifying clinically meaningful and clinically substantial changes as assessed with commonly used outcome measures for depression to facilitate the translation of clinical trial results into clinical practice.